1, 1, 2-Trifunctionalization of terminal alkynes by imine/borane frustrated Lewis pairs. Issue 16 (11th July 2022) - Ullah, Aziz; Chen, Guo-Qiang
Abstract : The first metal-free 1, 1, 2-trifunctionalization of terminal alkynes is reported, providing a straightforward means to synthesize trisubstituted-alkenyl boranes. Abstract : A metal-free one-pot 1, 1, 2-trifunctionalization of terminal alkynes with imines and boranes is reported. The reaction proceeds via an FLP deprotonation and alkynyl borate 1, 2-migration sequence, without the need for any organolithium reagents or transition metal catalysts. In this reaction, the imine first acts as a base to facilitate the Csp –H activation of the terminal alkyne and the resulting iminium ion then acts as an electrophile to induce 1, 2-migration of the alkynyl borate. It provides a straightforward means to synthesize trisubstituted alkenyl boranes, which cannot be directly accessed by hydroboration, with excellent step and atom economy under mild conditions.